COMMENT LES TICE PEUVENT CONTRIBUER A L’EVALUATION EN CLASSE DE LANGUES - MAUREL, Rodolphe (Acta et Commentationes, Sciences of Education, 2019)
Two issues are discussed in this article. Ways for ICT-based differentiated evaluation in language classes and the impact of ICT on daily work of language teachers. The framework of the article is defined by Common European Reference Framework for languages. The importance to teach foreign languages in a contextualized way is underlined. For this aim the students have to be accustomed and permanently trained in understanding and oral production in the frame of ICT-based classroom